Morality through the lens of Confucian heritage countries: collective self variations and moral worldviews - Takamatsu, Reina; Park, Joonha; Matsuo, Akiko (Frontiers in Psychology, 2024)
The issue of Western, Educated, Industrialized, Rich, and Democratic (WEIRD) samples dominating research has been ongoing for decades, and now the emerging trend is to turn to theoretical perspectives from the Majority World. Adopting Western-centric methods based on reductionism can overlook important details and differences between similar cultures, particularly in East Asian cultures, where the Confucian values of relational harmony take many forms. We discuss a novel theoretical perspective on moral constitutions in Confucian heritage cultures. Our central tenet is that divergent moral concepts and ideals are present in Confucian cultures because each culture emphasizes a specific pillar and the self is situated differently in the social relationships that define the scope of interpersonal moral obligations. We consider three Confucian countries: China, Japan, and South Korea as examples. Despite geographical proximity and conventional categorization in cultural psychology, each Confucian country manifests distinct patterns of the self, moral ideals, and behavior in socio-moral contexts. To understand how and why moral worldviews vary within a region, we need to examine how the self in socio-cultural contexts differs and guides interpersonal norms and behaviors across sociocultural contexts. We conclude this paper by offering methodological recommendations for including indigenous moral concepts outside the WEIRD context.